The bile salt deoxycholate induces Campylobacter jejuni genetic point mutations that promote increased antibiotic resistance and fitness - Talukdar, Prabhat K.; Crockett, Torin M.; Gloss, Lisa M.; Huynh, Steven; Roberts, Steven A.; Turner, Kyrah L.; Lewis, Sebastien T. E.; Herup-Wheeler, Tristin L.; Parker, Craig T.; Konkel, Michael E. (Frontiers in Microbiology, 2022)
Oxidative damage to DNA is a significant source of mutations in living organisms. While DNA damage must be repaired to maintain the integrity of the genome and cell survival, errors made during DNA repair may contribute to evolution. Previous work has revealed that C. jejuni growth in the presence of bile salt deoxycholate (DOC) causes an increase in reactive oxygen species and the occurrence of 8-oxo-deoxyguanosine (8-oxo-dG) DNA lesions. The fundamental goal of this project was to determine if C. jejuni growth in a medium containing DOC contributes to DNA mutations that provide a fitness advantage to the bacterium. Co-culture experiments revealed that C. jejuni growth in a DOC-supplemented medium increases the total number of ciprofloxacin-resistant isolates compared to C. jejuni grown in the absence of DOC. We recovered an isolate grown in a medium with DOC that had a point mutation in the gene encoding the EptC phosphoethanolamine transferase. Transformants harboring the EptC variant protein showed enhanced resistance to the antimicrobial agent polymyxin B and DOC when compared to an eptC deletion mutant or the isolate complemented with a wild-type copy of the gene. Finally, we found that a deletion of mutY, which encodes an enzyme involved in the DNA base-excision repair pathway and repair of oxidative DNA damage, results in a mutator phenotype leading to an increased number of ciprofloxacin-resistant isolates. We postulate that DOC is a driver for DNA mutations (adaptations) and that the variants with enhanced fitness are enriched in animals, including poultry.